Speed Versus Accuracy: Implications of Adolescents' Neurocognitive Developments in a Digital Game to Train Executive Functions. Issue 1 (25th February 2019) - Homer, Bruce D.; Ober, Teresa M.; Rose, Maya C.; MacNamara, Andrew; Mayer, Richard E.; Plass, Jan L.
ABSTRACT: Adolescence is a period of rapid cognitive change, including an initial increase in speed of cognitive processing and a more gradual increase in efficiency of cognitive processing. This study examined how neurophysiological changes associated with adolescent development can inform the design of game‐based executive function (EF) training. Two versions of a digital game designed to train the EF subskill of inhibition were given to adolescents (aged 13–17; N = 96): one focusing on speed, the other on accuracy. Consistent with neurocognitive developments, it was hypothesized that younger adolescents would benefit more from the speed version, and older adolescents more from the accuracy version. A significant age by condition interaction was found: Controlling for pretest, younger adolescents had better outcomes in the speed condition, while older adolescents had better outcomes in the accuracy condition. These findings argue for consideration of adolescents' neurocognitive development when designing games for learning and skill improvement.